New frontiers in conflict management, peace economics and peace science - Chatterji, Madhumita; Gangopadhyay, Partha (Contributions to conflict management, peace economics and development ;, 2021)
New Frontiers in Conflict Management, Peace Economics and Peace Science explores the uncharted land of conflicts, human security and peace. Bringing together a diverse, world-leading researchers, this 29th volume of Contributions to Conflict Management, Peace Economics and Development focuses on some of the most serious challenges to human security posed by intra-state conflict and terrorism, interstate wars, predatory globalisation, failed development, poverty and inequality, environmental problems and climate shocks, inefficient governance and man-made and natural disasters. In so doing, this book contributes to the crafting of well-grounded academic and policy responses to global problems that urgently require novel solutions. For its breadth and depth of research, this book is essential reading for researchers working in peace studies, conflict studies, sustainability studies and economics. It is also of keen interest to policymakers in all of these areas.